(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the manifestations of multilingualism and language contact in Uzbekistan’s press and mass media. Uzbek society is characterized by a complex multilingual environment in which Uzbek, Russian, English, and other languages interact across various domains. The study analyzes how state and non-state media implement multilingual practices, including parallel multilingualism, asymmetric code-switching, and stylistically motivated code-mixing. Special attention is given to the functional differentiation of languages in journalistic texts, the stylistic contrast between official and independent media, and the role of abbreviations, quotations, and international terminology. The findings demonstrate that while official media maintain strict adherence to Uzbek as the primary language of communication, independent outlets employ more flexible linguistic strategies. Overall, multilingual practices in Uzbek media serve both communicative and stylistic functions, contributing to broader audience reach and enhanced textual expressiveness.